TOTAL INDIVIDU DAN KEPADATAN POPULASI BANGGAI CARDINALFISH (BCF) DI PERAIRAN KILOMETER LIMA LUWUK, KABUPATEN BANGGAI - Osmar Buatan; Novalina Serdiati; Abdul Masyahoro (Jurnal Biosilampari : Jurnal Biologi, 2022)
Periodic monitoring of the population is needed to see the effectiveness and success of interventions to maintain the BCF population in their habitat. This research was conducted in Kilometer Lima Waters, Luwuk Banggai Regency, Central Sulawesi Province from November to December 2021. Research stations were determined based on information on the distribution and presence of BCF using a belt transect. The observed data were then processed to determine the total individual and BCF density per transect. BCF density per observation point (transect) was calculated by calculating the average fish density from the fish density value of each transect. The total observations of Banggai Cardinalfish individuals observed at the study site were 1,232 individuals. While the density ranges from 0.49 ind/m-5.55 ind/m. The lowest density was observed on transect V (five) while the highest density was observed on transect II (two).